Optimal Design of the Connecting Rod of Vibration Grinding Mills Based on Ansys Workbench - Kuang Chi; Li Jing; Hu Junfeng; Li Hui (Jixie chuandong, 2023)
In order to solve the problem of fracture failure of the existing vibration grinding mill connecting rod within the design service life, the structural optimization design of the connecting rod is proposed. Firstly, the kineto-static analysis is used to solve the external force applied to the crank-slider mechanism in one motion cycle, which is used as the theoretical basis for the subsequent strength analysis. Secondly, Ansys Workbench is used to complete the static strength analysis and fatigue strength analysis of the connecting rod. It is determined that the failure of the connecting rod is caused by insufficient fatigue strength. Finally, the response surface methodology is used to optimize the design of the connecting rod. The objective of the optimization is to minimize the mass of the connecting rod, and the optimized constraint is that the fatigue strength of the connecting rod meets the standard. This optimization design determines the appropriate transition fillet radius, thin end ring thickness and shaft width. The maximum tensile load equivalent stress of the optimized connecting rod is reduced by 58.7%, and the fatigue life is increased by 1.4 times. The optimized connecting rod meets the operation requirements.